Linking Grain Mineral Content to Pest and Disease Resistance, Agro-Morphological Traits, and Bioactive Compounds in Peruvian Coffee Germplasm - Choque Incaluque, Ester Maryeta; Cueva Carhuatanta, César Aldair; Carreraa Rojo, Ronald Pio; Maravi Loyola, Jazmín Yurema; Hermoza Gutiérrez, Marián; Cántaro Segura, Hector Baroni; Fernández Huaytalla, Elizabeth; Gutiérrez Reynoso, Dina Lidna; Quispe Jacobo, Fredy Enrique; Ccapa Ramírez, Karina Beatriz (MDPI, 2026)
Mineral composition modulates plant health, agro-morphological attributes, and functional quality in coffee, yet large-scale evaluations remain limited. In 150 Coffea arabica L. accessions, we quantified grain minerals (Ca, K, Mg, Na, P, Zn, Cu, Fe, Mn); resistance to coffee leaf miner (CLM), coffee berry borer (CBB), and coffee leaf rust (CLR); agro-morphological traits; bioactive compounds (phenolics, flavonoids, chlorogenic acid, trigonelline, caffeine); and antioxidant capacity (ABTS, DPPH, FRAP). Mn and Zn were associated with greater resistance to CBB and CLM, whereas P and Ca related with lower susceptibility to CLR; a P–Zn antagonism emerged as a critical nutritional axis. Phosphorus was linked to larger size and higher 100-bean mass; Ca and Mg to greater fruit number and fruit mass per plant; and Fe to improved filling and higher 100-bean mass in parchment coffee. For bioactive compounds, P and K were positively associated with total phenolics, total flavonoids, caffeine, and ABTS/FRAP antioxidant activity, while trigonelline and chlorogenic acid correlated positively with the micronutrients Zn, Cu, and Fe. Cluster analysis resolved groups associated with resistance, Zn/Fe biofortification, productivity, and functional quality. PER1002287, PER1002216, PER1002207, and PER1002197 emerged as promising accessions balancing plant health, yield, and phytochemical quality. Overall, grain mineral composition is linked to plant health, productivity, and functional quality in coffee, providing a foundation for precision nutrient management and breeding programs aimed at resilient and high–value-added coffee.